In situ synchrotron XRD investigation of the dehydration and high temperature carbonation of Ca(OH)21. Issue 38 (14th October 2015) - Materić, V.; Ingham, B.; Holt, R.
<x xml:space="preserve">Abstract</x> In situ powder XRD investigation of the mechanisms of Ca(OH)2 dehydration and high temperature carbonation, focusing especially on the "superheating" phenomenon.